The Image of Nero in the Prado Museum, from the Perspective of a Historian of Antiquity - Fernández Uriel, Pilar (Eikón / Imago, 2018)
Nero, due to his personality and image, is a singular, disturbing and controversial figure, being the object of studies and interpretations of very different consideration in both History and Art over more than two thousand years. The current paper analyze his representation in the works of art deposited in the Prado National Museum, in painting and sculpture of different artists, in a chronological sequence comprised between the 16th and 20th centuries that show a Nero at different transcendental, controversial and even imaginary moments of his life.